Analysis of Digital Infrastructure Competitive Advantage through Capital Raising Strategy: VRIO Case Study at PT Sinergi Inti Andalan Prima Tbk (INET) - Muhammad Fathurrahman; Dini Mustika Buana Putri; Jufri Yandes (Universitas Mohammad Husni Thamrin, 2026)
The increasingly rapid development of digital technology has driven significant growth in the internet business sector. Digital transformation across various sectors, including education, banking, healthcare, e-commerce, and the creative industry, has increased the need for fast, stable, and high-capacity internet connectivity. The emergence of new technologies such as 5G, Wi-Fi 7, the Internet of Things (IoT), Artificial Intelligence (AI), and cloud computing is further expanding internet business opportunities. This study aims to analyze the effectiveness of the corporate action undertaken by PT Sinergi Inti Andalan Prima Tbk (INET) in supporting digital infrastructure expansion. Using the Resource-Based View (RBV) as an analytical lens, this study examines how the transformation of financial resources into technological assets (Wi-Fi 7) and the strengthening of international backbone infrastructure contribute to the creation of competitive advantage. Furthermore, the analysis applies the VRIO framework to evaluate the strategic characteristics of these assets in terms of being valuable, rare, inimitable, and organized. The findings indicate that investments in Wi-Fi 7 technology and ownership of international submarine cable access provide significant value in enhancing service quality (valuable), remain relatively limited in the domestic market (rare), and are difficult to replicate due to high capital requirements and complex technical capabilities (inimitable). In addition, the firm’s ability to effectively manage and integrate these resources (organized) strengthens its potential to achieve sustained competitive advantage. Overall, this strategy reflects a form of vertical integration aimed at capturing the retail market in strategic regions (Bali–Lombok), while simultaneously mitigating financial risks associated with reliance on debt financing.